The meritocratic paradox: Confucian democracy and the crisis of procedural legitimacy in contemporary South Korea - Jun, Hyungjoon; Lee, Hyun Jung (Asian Journal of Comparative Politics, 2025)
This article explores the paradoxical dynamics of Confucian meritocracy and democratic legitimacy in contemporary South Korea. Despite democratic consolidation through the Candlelight Revolution (2016–2017), Korea's political landscape remains marked by hierarchical cultural norms rooted in Confucian traditions. Drawing on Jürgen Habermas's discourse ethics and Stephen Angle's Progressive Confucianism, this study examines how meritocratic discourses shape civic attitudes and institutional practices in ways that both support and undermine democratic legitimacy. The article demonstrates that contemporary Confucian meritocracy often produces systematically distorted communication, excluding citizens from participatory deliberation. The analysis interrogates Confucian values’ role in recent democratic crises, including President Yoon Suk-yeol's 2024 martial law declaration, showing how meritocratic rhetoric justified anti-democratic measures. However, the study reveals potential for Confucian ethical resources to reinforce democratic values when critically reconstructed through communicative action. The Korean case illustrates the struggle to reconcile inherited cultural traditions with democratic ideals, highlighting the importance of institutional frameworks balancing moral excellence with political equality. This contributes to debates on post-Confucian democracy by emphasizing that legitimacy hinges not on rejecting tradition but on subjecting all political claims to rational scrutiny through inclusive democratic discourse.
CRIS-Team Scopus Importer:2025-11-28
Keywords: comparative action; Confucian meritocracy; democratic legitimacy; discourse ethics; progressive Confucianism; South Korean politics